A Longitudinal Study of Income Differences in the Height-BMI Relation among U.S. Children Ages 6 to 14. (1st September 2016) - Murasko, Jason E.
ABSTRACT: Previous work has shown a positive height-obesity association in U.S. children that is more pronounced in those from lower-income families than in those from higher-income families. That work has been limited to cross-sectional analysis. This study evaluates income differentials in the inter-temporal associations between childhood height and obesity in U.S. children ages 6 to 14. Pooled samples of 9, 670 female and 10, 110 male children from the U.S. Early Childhood Longitudinal Study—Kindergarten Cohort (ECLS-K) were evaluated in multilevel mixed effects models. The results indicated a modest height-income interaction such that the concurrent height-obesity association was weaker at higher incomes. This strengthened into adolescence for females and weakened for males. With respect to height growth, for lower-income males, being shorter before the typical start of the growth spurt (≈ 9 years) and experiencing faster later growth (between 11 and 14 years) were attributes less strongly associated with subsequent obesity. There were no indicated income interactions with height growth in females.